The Roles of MicroRNAs in Tendon Healing and Regeneration - Ding, Lingli; Wang, Min; Qin, Shengnan; Xu, Liangliang (Frontiers in Cell and Developmental Biology, 2021)
Tendons connect the muscle abdomen of skeletal muscles to the bone, which transmits the force generated by the muscle abdomen contraction and pulls the bone into motion. Tendon injury is a common clinical condition occurring in certain populations, such as repeated tendon strains in athletes. And it can lead to substantial pain and loss of motor function, in severe cases, significant disability. Tendon healing and regeneration have attracted growing interests. Some treatments including growth factors, stem cell therapies and rehabilitation programs have been tried to improve tendon healing. However, the basic cellular biology and pathology of tendons are still not fully understood, and the management of tendon injury remains a considerable challenge. Regulating gene expression at post-transcriptional level, microRNA (miRNA) has been increasingly recognized as essential regulators in the biological processes of tendon healing and regeneration. A wide range of miRNAs in tendon injury have been shown to play vital roles in maintaining and regulating its physiological function, as well as regulating the tenogenic differentiation potential of stem cells. In this review, we show the summary of the latest information on the role of miRNAs in tendon healing and regeneration, and also discuss potentials for miRNA-directed diagnosis and therapy in tendon injuries and tendinopathy, which may provide new theoretical foundation for tenogenesis and tendon healing.